Evolution of Studies on Creativity - Machado, Luiz Alberto de Souza Aranha (Farol, 2024)
This article aims to describe the evolution of studies on creativity and innovation, covering their main concepts and definitions, as well as the connection between creativity and innovation, emphasizing the transformation of creativity from an individual attribute to an attribute focused on social concerns and the formulation of public policies.